Early Islamic law in Basra in the 2nd/8th century. Aqwal Qatadah b. Da'amah al-Sadusi - Al-Salimi, Abdulrahman (Islamic history and civilization, 2017)
The manuscript of the 'Aqwal Qatada' has repeatedly attracted particular interest among modern scholars, as it raises questions concerning the early development of the 'Ibadi' Basran community and the emergence of Islamic jurisprudence in Iraq. It is a unique document because it attests to the existence of a scholarly link between 'Sunnis' and 'Ibadis' during the early development of Islamic law. The fact that the legal responsa and traditions of Qatada b. Di'ama al-Sadusi (60/680-117/735) are part of an 'Ibadi' collection, in which the traditions of Ibadi Imam Jabir b. Zayd (d. 93/ 711) have been transmitted through 'Amr b. Harim and 'Amr b. Dinar, proves that the Ibadi lawyers of the first generations considered Qatada to be a faithful upholder of Jabir's doctrine. Given the lack of material available for 'Jabir', instructions must have been given to collect whatever was transmitted through Qatada. Qatada's legal responsa must have corresponded to those of the first Ibadi authorities, which explains why the collator of the Aqwal Qatada (probably Abu Ghanim al-Khurasani) included them in an Ibadi manuscript. The present volume sheds light on the relationship between the 'Aqwal Qatada 'and 'Ibadi' authorities such as al-Rabi, Abu Ubayda, and Jabir.